Host integrity monitoring using Osiris and Samhain - Wotring, Brian; Potter, Bruce; Ranum, Marcus J. (Rockland, MA : Syngress, 2005)
This book will walk the reader through the process of preparing and deploying open source host integrity monitoring software, specifically, Osiris and Samhain. From the configuration and installation to maintenance, testing, and fine-tuning, this book will cover everything needed to correctly deploy a centralized host integrity monitoring solution. The domain includes home networks on up to large-scale enterprise environments. Throughout the book, realistic and practical configurations will be provided for common server and desktop platforms. By the end of the book, the reader will not only understand the strengths and limitations of host integrity tools, but also understand how to effectively make use of them in order to integrate them into a security policy. * Brian Wotring is the creator of Osiris. He speaks and writes frequently on Osiris for major magazines, Web sites, and trade shows. And, the book can be prominently marketed from the Osiris Web site * This is the first book published on host integrity monitoring, despite the widespread deployment of Osiris and Samhain * Host Integrity Monitoring is the only way to accurately determine if a malicious attacker has successfully compromised the security measures of your network.
Chapter 1: Fundamentals; Chapter 2: Understanding The Terrain In order to be effective at understanding what to monitor; Chapter 3: Threats; Chapter 4: Planning The key to obtaining the most out of the adoption of host integrity tools; Chapter 5: Osiris; Chapter 6: Samhain; Chapter 7: Analysis and Response; Appendix A: Monitoring Linksys Devices Appendix B: Advanced Strategies.
Includes index.
Keywords: Computer networks -- Security measures; Electronic books